Práce v kotli: (Re)produkce opozice fotbalových fanoušků v moderních mantinelech - Pařízková, Alena; Šusta, David (Lidé města, 2015)
Professional football as a globalised sport is increasingly shaped by the processes of McDonaldisation. Specific places in football stadiums known as the “kotel” became the last asylum for opposition to this development. We grasp the interconnection of sites and individuals in the contexts of different ideologies, and power relations through the perspective of those football fans known as the ultras. Based on the ethnographic research of the fans of the AC Sparta Football Club, the article shows that Spartan ultras are formed mainly around three basic points: carnival, “kotel”, and traditions. Carnival is a way of cheering, “kotel” is a place of practice, and tradition means authenticity, community and continuity. The declared principles of cheering assist in shaping the fans’ authenticity and tribal belonging, thus creating a basis for sovereignty. They define their position in the unequal power hierarchy of professional football in terms of tradition, authenticity and independence, which stands as dichotomous and contradictory to modern consumerism. However, many of their activities are modern and glocal.